Persepsi Petani terhadap Pertanian Zero Waste Farming pada Integrasi Kambing di Lahan Perkebunan Lada yang Menggunakan Penyanggah Pohon Gamal - Syahrir Syahrir; Muhtar Amin; Nurmini Nurmini; Junaedi Junaedi (Musamus Journal of Livestock Science, 2022)
This study aims to determine the level of perception of farmers in the application of zero waste farming systems on the integration of goats on pepper plantations using gamal tree supports. The observed variables are; perception of zero waste, innovation, productivity, technical, economic, environmental and social, waste management, added value, feasibility, and aspects of risk of loss. The perception value category consists of 5 levels, namely; very high, high, low and very low. Farmers' perception of zero waste agriculture is high (79.6%), innovation is very high (87.6%), productivity is very high (94.8%), technical perception is high (69 .2%), economic perception level is very high (90.8%), environmental and social perception level is high (67.6%), waste treatment level is very high perception (97.6%), value added perception level is very high ( 96,8%), the feasibility of the perception level is very high (85.6%), and the risk aspect of the loss has a high perception level (79.6%). The level of perception is high on the aspect of the zero waste perception indicator, technical, environmental and social, and the risk of loss aspect and very high on the aspect of the zero waste perception indicator, innovation, productivity, economy, waste management, added value, and feasibility.